Online interactivity: best practice based on two case studies - Tom Boyle; John Cook (Association for Learning Technology, 2001)
This paper compares the experiences of two studies in the use of network supported collaborative learning. These studies aimed to enhance the learning experience of traditional campus-based students. The courses used a hybrid of face-to-face contact and collaborative work mediated through electronic networks. The aim of the studies was to provide an enhanced educational experience to these traditional student cohorts.